2015
DOI: 10.1093/mnras/stv1439
|View full text |Cite
|
Sign up to set email alerts
|

Symplectic integration for the collisional gravitationalN-body problem

Abstract: We present a new symplectic integrator designed for collisional gravitational N -body problems which makes use of Kepler solvers. The integrator is also reversible and conserves 9 integrals of motion of the N -body problem to machine precision. The integrator is second order, but the order can easily be increased by the method of Yoshida. We use fixed time step in all tests studied in this paper to ensure preservation of symplecticity. We study small N collisional problems and perform comparisons with typicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…As shown in Hernandez & Bertschinger (2015), HB15 conserves angular momentum exactly. WHJ has analogous operators A h , B h , and C h of eq.…”
Section: Overview Of Hb15 and Comparison With Wisdom-holman Methodsmentioning
confidence: 77%
See 4 more Smart Citations
“…As shown in Hernandez & Bertschinger (2015), HB15 conserves angular momentum exactly. WHJ has analogous operators A h , B h , and C h of eq.…”
Section: Overview Of Hb15 and Comparison With Wisdom-holman Methodsmentioning
confidence: 77%
“…For HB15, A † h/2 = A h/2 , and twice as many Kepler solver evaluations will be needed, 8 total. Hernandez & Bertschinger (2015) found that the time-reversible method φ 2 h performed better than φ h , even though they are both second order accurate.…”
Section: Overview Of Hb15 and Comparison With Wisdom-holman Methodsmentioning
confidence: 95%
See 3 more Smart Citations